Efficient Method for Color Iris Localization - G. Daway, Esraa; E.George, Loay; Sh.Hamoudi, Radhi (Iraqi Journal of Science, 2023)
Iris detection is considered as challenging image processing task. In this study efficient method was suggested to detect iris and recognition it. This method depending on seed filling algorithm and circular area detection, where the color image converted to gray image, and then the gray image is converted to binary image. The seed filling is applied of the binary image and the position of detected object binary region (ROI) is localized in term of it is center coordinates are radii (i.e., the inner and out radius). To find the localization efficiency of suggested method has been used the coefficient of variation (CV) for radius iris for evaluation. The test results indicated that is suggested method is good for the iris detection.